The development of soil quality using biochar amendment from agricultural waste - Daosukho, Saijit; Rodprasert, Soraya (Bulletin of Applied Sciences, 2015)
The development of highland soil quality using biochar amendment from agricultural waste was aimed to utilize the use of agricultural biomass as the substitution of chemical in agricultural fields. The experiment was conducted by pyrolysis biochar from durian shell, banana peel, and macadamia shell at low temperature (< 400 degree celcius) using Anila stove type gasifier. The biochar obtained in this study had the pH in the range of 7-10 depend on the type of raw materials. Each type of biochar was added to the highland soil from Phuruea, Loei Province, Thailand to study the liming effect. It was found that the 5% wt addition of biochar increased the pH of soil from 6 to 7, and biochar treated soil had more stability than the lime treatment at the same application rate. Moreover, the 5%wt of biochars were then added to the olive tree experiment plot at the Highland Agriculture Research and Development Center, Phuruea, Loei Province. After a year of application, the soil was collected and characterized. The results showed that the biochar application increased the pH of the soil to neutral range and also significantly increased the moisture, organic matter and potassium in soil in compared with non-treated soil.